2020
DOI: 10.1016/j.ymssp.2020.106880
|View full text |Cite
|
Sign up to set email alerts
|

On hysteresis modeling of a piezoelectric precise positioning system under variable temperature

Abstract: On hysteresis modeling of a piezoelectric precise positioning system under variable temperature. (2020) Mechanical Systems and Signal Processing, 145. 1-27.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Previous research has demonstrated that temperature variations change the amplitude but not the shape of the hysteresis loop when driven at low frequencies [14]. Thus, the hysteresis curve normalized by amplitude was consistent at each temperature.…”
Section: Voltage Displacement and Charge Displacement Curves Of The Pesa With/without Forced Liquid Coolingmentioning
confidence: 55%
See 1 more Smart Citation
“…Previous research has demonstrated that temperature variations change the amplitude but not the shape of the hysteresis loop when driven at low frequencies [14]. Thus, the hysteresis curve normalized by amplitude was consistent at each temperature.…”
Section: Voltage Displacement and Charge Displacement Curves Of The Pesa With/without Forced Liquid Coolingmentioning
confidence: 55%
“…Changes in the voltage displacement characteristics of a PESA due to the temperature variation when a voltage is input quasi-statically have been reported [14,15]. However, there are no reports on the hysteresis characteristics, and frequency characteristics during large-amplitude, high-frequency, and continuous driving, where heat generation, which cannot be dealt with by natural heat dissipation, is a problem [16].…”
Section: Introductionmentioning
confidence: 99%
“…[90][91][92] Physical-based modeling and robust control have also been successfully implemented on tetethered microrobotic systems, demonstrating their potential to guarantee the performance of these robotic systems despite strong environment changes. [93,94] To further improve capabilities, research on integrated sensors that are able to provide high-quality measurement close to the point of contact between robot and object it is interacting with has also been pursued. [95][96][97] In addition, novel actuation principles based on smart materials and associated kinematic designs are being investigated.…”
Section: Motivation For 4d Printing In Microrobotics 21 Microrobotics State Of the Artmentioning
confidence: 99%
“…Mostly it focuses on the material properties and the lack of research on the background of structure-integrated piezoelectric sensor-actuators, which means that the research on structural integrated piezoelectric sensor-actuators and their control systems is very scarce. In the existing related research on structural integrated piezoelectric sensor-actuators, the difficulties with the inverse hysteresis model [ 37 ] and the poor output accuracy of the actuator [ 38 ] are still to be solved. Therefore, based on research on the structure-integrated piezoelectric sensor-actuator, this paper presents a dynamic hysteresis model based on building a nonlinear control system to achieve the displacement correction of the microsystem after sensing, which provided a fine application foreground for a structure-integrated piezoelectric sensor-actuator in a micro high-precision integrated system.…”
Section: Introductionmentioning
confidence: 99%